2015
DOI: 10.3928/01484834-20150417-05
|View full text |Cite
|
Sign up to set email alerts
|

Does Prior RN Clinical Experience Predict Academic Success in Graduate Nurse Practitioner Programs?

Abstract: These findings serve as a building block of empirical evidence for admissions committees as they consider entry requirements for NP programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…The results showed that there was no relationship between the outcome variables for academic success: cumulative GPA, clinical course GPA, and course failures or academic probation. When compared to students with less academic experience, those with more academic experience were less likely to graduate in 4 years (El‐Banna et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that there was no relationship between the outcome variables for academic success: cumulative GPA, clinical course GPA, and course failures or academic probation. When compared to students with less academic experience, those with more academic experience were less likely to graduate in 4 years (El‐Banna et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of the first 2 years of the certified midwife program at the State University of New York Health Science Center at Brooklyn found that no student midwives withdrew or were dismissed from the program . Studies that have evaluated nurse practitioner students similarly found that type of nursing preparation and whether or not a student had a previous advanced degree were not related to student success …”
Section: Discussionmentioning
confidence: 99%
“…Completion was chosen as the most relevant measure, but noncompletion is higher than the more frequently cited attrition, making comparison difficult . A study of factors related to completion of one institution's on‐site nurse practitioner programs found that while 77% of students overall graduated within 4 years, only 44% of African American students did, suggesting that subgroups of students are more likely not to complete graduate health programs …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations